Longitudinal impact of volunteering on the cognitive functioning of older adults: A secondary analysis from the US Health and Retirement Study - Ester Villalonga-Olives; Kayleigh R. Majercak; Josue Almansa; Tasneem Khambaty (Elsevier, 2023)
Objectives: To examine the relationship of volunteering with cognitive activity, social activity, and physical activity among older adults and, ultimately, with later cognitive functioning across different time periods. Methods: We used individual responding to three waves of the US Health and Retirement Study panel data from 2008, 2012, and 2016 (n = 2,862). Self-reported questionnaires were used to assess annual volunteering frequency (non volunteering, volunteering <100 h and ≥100 h), and an adapted version of the Telephone Interview for Cognitive Status (TICS) was used to assess memory, mental processing, knowledge, language, and orientation. A structural equation model was estimated to assess effects on cognitive functioning throughout waves. Results: Those participants that were part of volunteering activities in 2012 showed an increase between 2008 and 2012 in moderate physical activity (β = 0.19, P < 0.001 for those volunteering less than 100 h and β = 0.21, P < 0.001 for those volunteering at least 100 h), increase in social activity (β = 0.10, P = 0.052 for those volunteering less than 100 h and β = 0.12, P = 0.018 for those volunteering at least 100 h) and increase in higher cognitive activity (β = 0.13, P < 0.001 for those volunteering at least 100 h), compared to participants who did not volunteer. Higher levels of cognitive activity in 2008 and 2012 were associated with higher cognitive functioning on the following waves (β = 0.66 and β = 0.60, P < 0.001, respectively). Discussion: Volunteering is a modifiable activity that can be increased to bolster cognitive functioning in older adulthood, primarily mediated by increased cognitive activity.